Simultaneous analysis of Ba and Sr to Ca ratios in scleractinian corals by inductively coupled plasma optical emissions spectrometry - Cantarero, Sebastian I. (2017)
Chemical analyses of coral skeletons are useful for reconstructing past ocean conditions. Simultaneous measurements of Ba and Sr to Ca ratios in coral samples have predominantly been achieved by inductively coupled plasma mass spectrometry (ICP-MS). We demonstrate a method that expands the application of the inductively coupled plasma optical emissions spectrometry (ICP-OES) technique to precisely analyze Ba, Sr, and Ca simultaneously. Analytical drift and matrix interferences at a range of Ba/Ca ratios (3–10 μmols/mol) were explored to determine the efficacy of standardized corrections. Minor disparity in drift and matrix interferences between standards of varying Ba/Ca ratios indicate that standardized corrections can be applied. Comparative analysis between ICP-OES and an established ICP-MS technique in a Singapore coral and international coral standard JCp-1 were utilized to validate the proposed ICP-OES technique. ICP-MS and ICP-OES techniques showed a consistent offset, which was correctible with the use of an internal lab standard and resulted in only minor differences between techniques. ICP-OES showed comparable accuracy and precision to the ICP-MS, as evaluated by analysis of JCp-1 which averaged values within one standard deviation of established concentrations (accurate to within 0.38 μmol Ba/mol Ca and 0.014 mmol Sr/mol Ca). We have demonstrated a sufficiently precise and accurate method for simultaneous analysis of Ba and Sr to Ca ratios in coral samples on an ICP-OES system. Expanding the application of ICP-OES in coral geochemical analysis provides a lower cost alternative to ICP-MS, while maintaining a high sample throughput.